Naplus: a software distributed shared memory for virtual clusters in the cloud. (24th February 2017) - Zeng, Lingfang; Wang, Yang; Kent, Kenneth B.; Xiao, Ziliang
Summary: Virtual clusters (VCs) have exhibited various advantages over traditional cluster computing platforms by virtue of their extensibility, reconfigurability, and maintainability. As such, they have become a major execution environment for cloud‐based cluster applications. However, compared with traditional clusters, their distributed‐memory programming paradigm still remains largely unchanged, which implies that cluster applications cannot be efficiently deployed in VCs, especially when virtual machines (VMs) are running in different physical hosts. Recently, some efforts have been made to improve inter‐VM communication, resulting in many studies on how cluster applications could take advantages of VCs. However, most of them mainly focus on the situation that the VMs are all coresident on the same physical machine where the message passing mechanism is usually optimized away by exploiting the host's shared memory. In this paper, we present a design and implementation of Naplus, a kernel‐based virtual machine approach to the inter‐VM communications that are across different physical hosts. Naplus is based on Nahanni, a mechanism for shared‐memory communication in virtual environments. As such, it not only inherits the major merits of Nahanni with respect to flexible data structures and efficient synchronization but also achieves a shared‐memory paradigm among VMs. With Naplus, we enable the size of shared space to be maximized as large as the sum of each machine's local memory to accommodate cluster applications with large memory footprints. We prototype Naplus in a dual‐host system where an empirical study is conducted to show the effectiveness of the Naplus approach in achieving distributed shared memory for VCs in data centers. Copyright © 2017 John Wiley & Sons, Ltd.